Tailoring Consent to Context: Designing an Appropriate Consent Process for a Biomedical Study in a Low Income Setting - Tekola, Fasil; Bull, Susan J.; Farsides, Bobbie; Newport, Melanie J.; Adeyemo, Adebowale; Rotimi, Charles N.; Davey, Gail (PLOS Neglected Tropical Diseases, 2009)
Author Summary Informed consent to biomedical research in developing countries is a highly topical issue. When consent forms and processes are simply borrowed from developed countries, obtaining genuine informed consent becomes extremely challenging. This paper examines how a quick and relatively simple intervention (Rapid Assessment) can influence the design and implementation of informed consent processes in the context of biomedical research involving poor, socially stigmatized and illiterate communities in a developing country. The paper goes on to discuss the effect of social, cultural, and economic factors identified by the intervention in a particular context and demonstrates how knowledge of these influences helped to develop a socially relevant and practical consent process prior to conducting a programme of community-based genetic research. The paper concludes that this intervention is an effective and economical means by which to ensure the efficacy and ethical integrity of consent processes when recruiting participants to new research sites, even within countries with which researchers are already acquainted.